Pendidikan Kesehatan Teknik Menyusui Pada Nyonya E di Klinik Bina Sehat Kabupaten Bantul - Setiawati, Lucki Dwi; Sri Sunarti, Nining Tunggal; Winarsih (Evidence Midwifery Journal, 2024)
The postpartum period is a recovery period after pregnancy and childbirth. This period is important for every woman who has just given birth because there are many changes and anxieties, one of the anxieties is not being able to provide breast milk properly to her baby. Providing health education on breastfeeding techniques is very helpful in overcoming anxiety. Health education on breastfeeding techniques can help maintain exclusive breastfeeding for six months, The aim of the research is to provide midwifery care during the postpartum period by providing Health Education on Breastfeeding Techniques to Mrs. E at the Bina Sehat Clinic, method this research is qualitative with case studies, the informants in this research are postpartum mothers who gave birth at the Bina Sehat Clinic, data collection used interviews, observation and documentation studies, results/findings of providing health education on breastfeeding techniques carried out on Mrs. E during postpartum midwifery care from six hour postpartum period to thirteenth day was successfully carried out with the result that the mother was able to apply correct breastfeeding techniques to her baby. Education Healthy breastfeeding techniques are carried out in accordance with standard operating procedures and have been implemented